Coverage and impact of influenza vaccination among children in Minhang District, China, 2013–2020 - Zhang, Zhaowen; Shi, Liming; Liu, Nian; Jia, Biyun; Mei, Kewen; Zhang, Liping; Zhang, XuanZhao; Lu, Yihan; Lu, Jia; Yao, Ye (Frontiers in Public Health, 2023)
Background Young children have a great disease burden and are particularly vulnerable to influenza. This study aimed to assess the direct effect of influenza vaccination among children and to evaluate the indirect benefit of immunizing children. Methods The influenza vaccination records for all children born during 2013–2019 in Minhang District and surveillance data for reported influenza cases were obtained from the Minhang CDC. 17,905 children were recorded in the vaccination system and included in this study. Descriptive epidemiology methods were used for data analysis, including an ecological approach to estimate the number of influenza cases averted by vaccination and linear regression to estimate the reduction in influenza cases in the general population per thousand additional childhood vaccination doses. Results During the study period, the annual vaccination coverage rate ranged from 10.40% in 2013–2014 to 27.62% in 2015–2016. The estimated number of influenza cases averted by vaccination ranged from a low of 0.28 (range: 0.23–0.34) during 2013–2014 (PF: 6.15%, range: 5.11–7.38%) to a high of 15.34 (range: 12.38–18.51) during 2017–2018 (PF: 16.54%, range: 13.79–19.30%). When increasing vaccination coverage rate by 10% in each town/street, a ratio of 7.27–10.69% cases could be further averted on the basis of observed cases. In four selected periods, the number of influenza cases in the general population was most significantly correlated with the cumulative childhood vaccination doses in the prior 2–5 months, and the reduction in influenza cases ranged from 0.73 to 3.18 cases per thousand additional childhood vaccination doses. Conclusion Influenza vaccination among children is estimated to have direct effects in terms of averted cases and might provide an underlying indirect benefit to the general population. Vaccination coverage in high-coverage areas should be further expanded to avert more influenza cases.